An optimized support vector machine for lung cancer classification system - Oyediran, Mayowa O.; Ojo, Olufemi S.; Raji, Ibrahim A.; Adeniyi, Abidemi Emmanuel; Aroba, Oluwasegun Julius (Frontiers in Oncology, 2024)
IntroductionLung cancer is one of the main causes of the rising death rate among the expanding population. For patients with lung cancer to have a higher chance of survival and fewer deaths, early categorization is essential. The goal of thisresearch is to enhance machine learning to increase the precision and quality of lung cancer classification.MethodsThe dataset was obtained from an open-source database and was utilized for testing and training. The suggested system used a CT scan picture as its input image, and it underwent a variety of image processing operations, including segmentation, contrast enhancement, and feature extraction.ResultsThe training process produces a chameleon swarm-based supportvector machine that can identify between benign, malignant, and normal nodules.ConclusionThe performance of the system is evaluated in terms of false-positive rate (FPR), sensitivity, specificity, recognition time and recognition accuracy.